The effect of intensity on 3-dimensional kinematics and coordination in front-crawl swimming - de Jesus, K.; Sanders, R.; de Jesus, K.; Ribeiro, J.; Figueiredo, P.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Physiology and Performance, 2016)
Background: